1993
DOI: 10.1038/icb.1993.22
|View full text |Cite
|
Sign up to set email alerts
|

Killing by cytotoxic T cells and natural killer cells: Multiple granule serine proteases as initiators of DNA fragmentation

Abstract: SummaryThe vectorial secretion of the contents of highly specialized cytoplasmic granules is of pivotal importance to the killing hy cytotoxic T cells and natural killer cells. The purification and biochemical characterization of some of the granule constituents, in particular the pore-forming protein perforin, had engendered the notion that the killing of cellular targets was largely an osmotic phenomenon analogous to the insult delivered by complement attack. However, the apparent absence of membrane perfora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…The transient release of p24 into culture supernatants was probably from viable and dying inoculum cells. Since cytotoxic T lymphocytes are thought to deliver lytic signals by triggering apoptosis in targets (33)(34)(35), our findings may have implications for the ability of HIV-specific cytotoxic T lymphocytes to eliminate intraplacental infected cells. Additionally, HIV-induced apoptosis of infected cells (36) may be inhibited when these cells are in intimate contact with placental tissue, thereby prolonging their period of potential HIV transmission to the fetal circulation.…”
Section: Discussionmentioning
confidence: 99%
“…The transient release of p24 into culture supernatants was probably from viable and dying inoculum cells. Since cytotoxic T lymphocytes are thought to deliver lytic signals by triggering apoptosis in targets (33)(34)(35), our findings may have implications for the ability of HIV-specific cytotoxic T lymphocytes to eliminate intraplacental infected cells. Additionally, HIV-induced apoptosis of infected cells (36) may be inhibited when these cells are in intimate contact with placental tissue, thereby prolonging their period of potential HIV transmission to the fetal circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism of vascular damage in SSc has long been investigated, it remains unclear. Several factors have been implicated to cause endothelial injury, including granzyme A and B [17][18][19][20], AECA [21,22] complement factors [23] and oxygen free radicals [24]. Recent findings in a study of skin biopsies of UCD 200 chickens and human SSc patients revealed that endothelial cell apoptosis is a primary event in the pathogenesis of SSc, possibly induced by AECA-dependent cellular cytotoxity (ADCC) [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…31 For this purpose, the granules of cytotoxic T cells contain numerous proteins, including granzymes, TIA-1, and perforin. Stimuli like IL-2 or the binding of CD28 act via protein tyrosine ki- nases to induce polarization of various cytotoxic Tcell organelles, including the cytolytic granules.…”
Section: Discussionmentioning
confidence: 99%